Quantitative asymptotic estimates for evolution problems. (May 2017) - Moscariello, Gioconda; Porzio, Maria Michaela
Abstract: We study a quantitative asymptotic, stability estimates for solutions to nonlinear evolution equations. More precisely, we measure the distance in time of a solution to a parabolic problem from a solution to a stationary one.